LIBRARY CATALOGUES AND BOOKS NOTATED IN PROBATE INVENTORIES OF THE 17TH AND 18TH CENTURIES AS SOURCES FOR RESEARCH ON PRIVATE LIBRARIES AND READING - REIMO, TIIU (Knygotyra, 2010)
Institute of Information Studies, Tallinn University, 25 Narva Road, 10120 Tallinn, Estonia E-mail: tiiu.reimo@tlu.ee The article treats library catalogues and book lists recorded in probate inventories as sources for studying book ownership and reading history in Estonia. Based on research literature, editions of source materials and practical experience in library work, the information about books in catalogues and probate inventories of the 17th and 18th centuries is analysed and the aspects that must be considered while interpreting the information are demonstrated. The author’s point is that data retrieved from archive records and printed sources must be carefully studied and complemented, when possible, with information from surviving books in order to get as authentic picture of intellectual communication in the past centuries as possible.